2016
DOI: 10.1002/cssc.201501303
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and Phosphorous Co‐Doped Graphene Monolith for Supercapacitors

Abstract: The co-doping of heteroatoms has been regarded as a promising approach to improve the energy-storage performance of graphene-based materials because of the synergetic effect of the heteroatom dopants. In this work, a single precursor melamine phosphate was used for the first time to synthesise nitrogen/phosphorus co-doped graphene (N/P-G) monoliths by a facile hydrothermal method. The nitrogen contents of 4.27-6.58 at% and phosphorus levels of 1.03-3.00 at% could be controlled by tuning the mass ratio of melam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(55 citation statements)
references
References 42 publications
1
54
0
Order By: Relevance
“…289 A microwave-assisted technique was used for the synthesis of a N-S dual-doped graphene electrode, which was further used for the development of an articial muscle. 290 Due to their large surface areas, good conductivity, reactivity, stability, enhanced electrochemical performance and good Li ion storage capability, N-S, 291,292 N-F, 293 N-Cl 294 and N-P 295,296 dual-doped graphene materials have been proven to be excellent electrodes for batteries and [292][293][294]296 supercapacitors 294,295 as well as superior catalysts. 293,297 4.7 Concluding remarks and future outlook…”
Section: Substitution Of Two Elements (Dual-doping)mentioning
confidence: 99%
“…289 A microwave-assisted technique was used for the synthesis of a N-S dual-doped graphene electrode, which was further used for the development of an articial muscle. 290 Due to their large surface areas, good conductivity, reactivity, stability, enhanced electrochemical performance and good Li ion storage capability, N-S, 291,292 N-F, 293 N-Cl 294 and N-P 295,296 dual-doped graphene materials have been proven to be excellent electrodes for batteries and [292][293][294]296 supercapacitors 294,295 as well as superior catalysts. 293,297 4.7 Concluding remarks and future outlook…”
Section: Substitution Of Two Elements (Dual-doping)mentioning
confidence: 99%
“…Nitrogen and phosphorus belong in the same family; therefore, they show higher electron-donating ability which further shows stronger n-type behaviour. 358 The defects induced by co-doping (N and P) is predicated to bring about a highly localized state which is close to the Fermi level, especially for electrocatalysis. 359 However, N and P-doped graphene can also be applied in DSSCs as metal-free electrocatalyst.…”
Section: Phosphorus-doped Graphene In Dsscsmentioning
confidence: 99%
“…However, as with the IL electrolyte with a high voltage window used, the power characteristics of extremely narrow micropores are still limited, especially under the condition of high specific power. With such a limitation mainly due to the large ionic size of IL, the ion transport resistance in the IL electrolyte is high, which causes a rapid decrease in capacitance, thereby affecting the rate performance of the SC (Kondrat et al, 2012;Merlet et al, 2012;Peng et al, 2014;Wen et al, 2016). Chen et al have found that the pore size region of the favorable capacitors, except for the micropore region, is the mesoporous region (pore size ≈ 2 to 3.5 times ion size of IL; Wang et al, 2016b).…”
Section: Introductionmentioning
confidence: 99%